Ni, Cr, and Fe surfaces corroded by molten ZnCl2. Issue 6 (10th December 2019) - Wang, Xueliang; Yin, Huiqin; Liu, Wenguan; Yu, Guojun; He, Jian; Tang, Zhongfeng; Yan, Long
Abstract: Understanding the corrosion of molten ZnCl2 on metal surfaces is significant for the corrosion protection of metals, sustainable use of molten salts, preparation of ZnO coatings, and so on. In this paper, surfaces of pure Ni, Cr, and Fe corroded by molten ZnCl2 were investigated. The results show that Ni suffered very slight corrosion, while Cr experienced more serious corrosion than Ni, but lighter corrosion than Fe. The morphology of the corrosion of Cr and Fe, respectively, presented pitting and intergranular corrosion characteristics. Furthermore, nanostructured ZnO coatings were obtained on the surfaces of Ni and Fe, but not on the surface of Cr. The ZnO coating on the Ni surface was doped with a small amount of Zn5 (OH)8 Cl2, and the ZnO coating on the Fe surface was doped with ZnFe2 O4 and Zn2 OCl2 . The coatings on the Ni and Fe surfaces had an average thickness of 1.5 and 50 μm, respectively. Abstract : Surfaces of pure Ni, Cr, and Fe corroded by molten ZnCl2 were investigated. The results show that Ni suffered very slight corrosion, while Cr experienced more serious corrosion than Ni, but lighter corrosion than Fe. The morphology of the corrosion of Cr and Fe, respectively, presented pitting and intergranular corrosion characteristics. Nanostructured ZnO coatings were obtained on the surfaces of Ni and Fe, but not on the surface of Cr.